The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2024
DOI: 10.9734/ajsspn/2024/v10i2258
|View full text |Cite
|
Sign up to set email alerts
|

Response of Biofertilizer and Biochar on Growth and Yield of Baby Corn

Yedoti Uma Maheswar,
Umesha C.

Abstract: The field experiment was conducted at Crop Research Farm, Department of Agronomy, Naini Agriculture Institute, SHUATS, Prayagraj, UP, during the Zaid season of 2023. The experiment was laid out in Randomized Block Design with ten treatment combinations which are replicated thrice. The experiment involves with the biofertilizers like azospirillum(10g and 20g/kg seed),azotobacter(10g and 20g/kg seed) along with biochar(0t/ha,10t/ha,40t/ha). Among the various treatment combinations in (treatment-9) with the appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Hanpattanakita et al [17] reported that the yield of red chili was significantly greater for the biochar-treated soil than in control plot. Dapa et al [18] also reported that the chilli fresh stem weight, leaf weight and fruit weight significantly increased by biochar addition [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Hanpattanakita et al [17] reported that the yield of red chili was significantly greater for the biochar-treated soil than in control plot. Dapa et al [18] also reported that the chilli fresh stem weight, leaf weight and fruit weight significantly increased by biochar addition [19][20][21].…”
Section: Discussionmentioning
confidence: 99%